International nursing research collaboration: Visualizing the output and impact of a Fulbright Award - Charlene Downing; Annie Temane; Susan Gerding Bader; Jean L Hillyer; Sean Christopher Beatty; Marie Hastings-Tolsma (Elsevier, 2021)
Fulbright Awards were initiated in 1946 and are designed to increase understanding between people of the United States and other countries through research, teaching, and/or practice. While hundreds of individuals have received such award, little is known about the impact of such engagement. The purpose of this study was to determine the extent and impact of a Fulbright Award by examining the primary publications emanating from research collaborations at one university. The paper presents global use of these primary works (n = 11) from 2012 to 2019 based on a bibliometric analysis of retrieved citations, as well as altmetric analyses. The primary referenced works included quantitative (n = 3), qualitative (n = 2), a review, and 5 discourse papers. Nine databases were searched to determine use of reference works. Analyses revealed that these primary sources were cited 42 times with lead authors most often from the South Africa or the United States. The main disciplines represented by first authors in these citing articles were nursing (n = 28, 66.6%), followed by midwifery (n = 11, 26.1%) and psychology/psychiatry (n = 8, 19%). Central keywords focused on healthcare systems, concept analysis, relationships, nursing/midwifery, and relationship centered. Citing articles were primarily quantitative (n = 15), qualitative (n = 11), reviews (n = 6), mixed methods (n = 1), and discourse papers which included concept analyses and policy papers n = 10). All papers demonstrated team science. Additional secondary analysis was conducted to identify the non-scientific use and potential impact of primary sources; three works demonstrated significant downstream utilization which correlated with those referenced citations with high citation counts. Determination of the extent to which scholarly works emanating from collaborative work by researchers impacted scientific and non-scientific sources provides powerful evidence of the value of a Fulbright Award. Additional qualitative research is needed to determine the less than obvious impact of presentations and non-scientific uses on Fulbright collaborations.